The prognostic role of epidermal growth factor receptor mutation in completely resected ampullary adenocarcinoma - Varol, Umut; Cakır, Ebru; Aktas, Safiye; Altun, Zekiye Sultan; Dilek, Fatma Husniye; Butun, Osman; Salman, Tarık; Unlu, Ayse Gulden Diniz; Alacacioglu, Ahmet; Somali, Isil (Polish Journal of Pathology, 2023)
The aim of this study is to make a differential diagnosis and prognosis of the ampullary adenocarcinoma subtypes. We also investigated the role of prognostic markers PD-1 and PD-L1, and epidermal growth factor receptor (EGFR). Local or locally advanced stage ampullary adenocarcinoma patients who had undergone pancreaticoduodenectomy at the time of diagnosis were included. MUC1, MUC2, MUC5AC, CDX2, CK7, CK20, PD-1, and PDL-1 were analysed immunohistochemically, and EGFR was analysed by real-time polymerase chain reaction. According to histopathological and immunohistochemical evaluation, we found 27 patients as pancreatobiliary type and 56 patients as intestinal type adenocarcinoma. The median survival of patients with intestinal and pancreatobiliary type adenocarcinoma was 23 months and 76 months ( p = 0.201), respectively. When the survival of PD1-positive ( n = 23) and PD-L1-positive ( n = 18) patients were compared with the patients with negative staining ( n = 60, n = 65), no significant difference was found. Epidermal growth factor receptor mutation was detected in a total of 6 patients, and 5 of these 6 mutations were shown in intestinal type tumours and one in a pancreatobiliary type tumour. A significant difference was determined in terms of overall survival for the patients with EGFR mutations compared to those without ( p = 0.008). In conclusion, we could reveal the prognostic significance of EGFR mutation, which is also a target molecule.